Respuesta :

Answer:

11. A) x = 0

y = 2x + 5

=> y = 2 * 0 + 5

=> y = 0 + 5 = 5

=> y = 5 (First blank)

x = 1

y = 2x + 5

=> y = 2 * 1 + 5

=> y = 2 + 5 = 7

=> y = 7 (Second blank)

x = 2

y = 2x + 5

=> y = 2 * 2 + 5

=> y = 4 + 5

=> y = 9 (Third blank)

x = 3

y = 2x + 5

=> y = 2 * 3 + 5

=> y = 6 + 5

=> y = 11 (Fourth blank)

x = 4

=> y = 2x + 5

=> y = 2 * 4 + 5

=> y = 8 + 5

=> y = 13 (Fifth blank)

11. B)  x = 0

=> y = [tex]3x^{2} + 1[/tex]

=> y = 3 * 0 * 0 + 1

=> y = 0 + 1

=> y = 1 (First blank)

x = 1

=> y = [tex]3x^{2} + 1[/tex]

=> y = 3 * 1 * 1 + 1

=> y = 3 + 1

=> y = 4 (Second blank)

x = 2

=> y = [tex]3x^{2} + 1[/tex]

=> y = 3 * 2 * 2 + 1

=> y = 12 + 1

=> y = 13 (Third blank)

x = 3

=> y = [tex]3x^{2} + 1[/tex]

=> y = 3 * 3 * 3 + 1

=> y = 27 + 1

=> y = 28 (Fourth blank)

x = 4

=> y = [tex]3x^{2} + 1[/tex]

=> y = 3 * 4 * 4 + 1

=> y = 48 + 1

=> y = 49 (Fifth blank)

For more info, here's a picture,

If my answer helped, kindly mark me as the Brainliest!!

Thank You!!

Ver imagen AayushTripathy
ACCESS MORE